Selected Predictors of Consumer Ethnocentrism in the Food Market (Gender Differences) - Paweł Bryła (MDPI AG, 2021)
This paper aims to identify predictors of consumer ethnocentrism in the food market. An online survey was conducted in a sample of 1000 Polish consumers, which was representative by sex, age, education level, urban–rural divide, and region. The 10-item CETSCALE was applied. In a retrograde stepwise regression model, consumer ethnocentrism in the food market was positively related to tradition and conformity Schwartz values, to the pride of being Polish, and to such product characteristics as the country of origin, distance from the producer, and natural content. It was negatively related to the universalism value and to being a student. To gain further insights into the predictors of consumer ethnocentrism in the food market for either gender, separate regressions were conducted among men and women. Three predictors affected positively and significantly consumer ethnocentrism in the food market both among men and among women, namely the tradition Schwartz value, pride of being Polish, and importance attached to distance covered by the food product from the producer to the shop, which is related to the preference for local food. Moreover, consumer ethnocentrism among men was dependent on their food choice motive–environmental friendliness, whereas consumer ethnocentrism among women was affected by the importance attached to the product’s country of origin, and it was negatively related to women’s younger age.